Enterococcus casseliflavus regulates amino acid metabolism in edible insect Clanis bilineata tsingtauica: a functional metagenomics study - Qian, Lei; Wang, Yanhui; Deng, Pan; Zhang, Jia; Qin, Yi; Li, Zongnan; Liao, Huaijian; Chen, Fajun (Frontiers in Microbiology, 2024)
Introduction The soybean hawkmoth, Clanis bilineata tsingtauica, is an edible insect that possesses high nutritional, medicinal and economic value. It has developed into a characteristic agricultural industry in China. Methods The dominant gut bacterium in diapause larvae of soybean hawkmoths was identified by metagenomics, and the effect of diapause time on gut microbiome composition, diversity and function was investigated. Results Enterococcus and Enterobacter were measured to be the dominant genera, with Enterococcus casseliflavus and Enterococcus pernyi being the dominant species. Compared to the controls, the relative abundance of E. casseliflavus and E. pernyi on day 14 was lower by 54.51 and 42.45%, respectively. However, the species richness (including the index of Chao and ACE) of gut microbiota increased on day 28 compared to controls. The gene function was mainly focused on carbohydrate and amino acid metabolism. Metabolic pathways annotated for amino acids on day 14 increased by 9.83% compared to controls. It is speculated that diapause soybean hawkmoths may up-regulate amino acid metabolism by reducing E. casseliflavus abundance to maintain their nutritional balance. Additionally, tetracycline, chloromycetin and ampicillin were screened as the top three antibiotics against E. casseliflavus. Discussion This study not only extends our knowledge of gut microbiome in soybean hawkmoths at the species level, but also provides an initial investigation of gene functionality in interaction with insect hosts.